2009
DOI: 10.1631/jzus.b0920153
|View full text |Cite
|
Sign up to set email alerts
|

Protective paracrine effect of mesenchymal stem cells on cardiomyocytes

Abstract: Abstract:Objective: The aim of this study was to test the protective effect of mesenchymal stem cells (MSCs) on cardiomyocytes in vitro and to investigate the anti-apoptotic signaling pathway. Methods: MSCs from Sprague-Dawley (SD) rats were separated and cultured. MSC medium was collected from MSCs cultured in serum-free Dulbecco's modified eagle medium (DMEM) under hypoxia. Cultured cardiomyocytes from neonatal SD rats were exposed to hypoxia/reoxygenation (H/R) and treated with MSC medium. The apoptotic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…5A has demonstrated that many cardiomyocytes within the newly formed myocardium were mitotically incorporated with BrdU, suggesting that the newly formed cardiomyocytes are ensured. Therefore, the beneficial structural sequelae by flk-1 pos pADSC are associated with neoangiogenesis in particular of microvasculature and myogenic formation of bone fide cardiac cells, rather than the anti-apoptotic or cardiac protective effects that have been proposed by others [27].…”
Section: Flk-1 Pos Padsc Induced Myogenesis and Angiogenesismentioning
confidence: 89%
“…5A has demonstrated that many cardiomyocytes within the newly formed myocardium were mitotically incorporated with BrdU, suggesting that the newly formed cardiomyocytes are ensured. Therefore, the beneficial structural sequelae by flk-1 pos pADSC are associated with neoangiogenesis in particular of microvasculature and myogenic formation of bone fide cardiac cells, rather than the anti-apoptotic or cardiac protective effects that have been proposed by others [27].…”
Section: Flk-1 Pos Padsc Induced Myogenesis and Angiogenesismentioning
confidence: 89%
“…Caspase-3 is one of the most pivotal effector caspases that is sequentially activated, autocatalyzed, and processed into activated fragments during apoptosis [31]. Level of cleaved caspase-3, the activated fragment, is regarded as an index of apoptosis intensity [32]. The results of flow cytometric detection indicated that HSYA reduced the apoptosis rate of the H9c2 cardiomyocytes subjected to A/R, and this anti-apoptotic state was notably blocked by ZnPP-IX.…”
Section: Discussionmentioning
confidence: 99%
“…While the clinical data are encouraging (Chen et al, 2004;Katritsis et al, 2005), controversies regarding the mechanisms responsible for the cardioprotective effects of MSCs remain. It was hypothesized that the paracrine effect of MSCs plays an important role in protecting cardiomyocytes and improving cardiac function post transplantation (Tang et al, 2005;Xu et al, 2007;Xiang et al, 2009). Insulin-like growth factor-1 (IGF-1) is one of the key cytokines secreted by MSCs post transplantation (Nagaya et al, 2005;Xu et al, 2007;Tao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%